Hematologic and lymphatic system toxicities associated with immune checkpoint inhibitors: a real-world study - Li, Na; Feng, Yong; Chen, XiaoLing; Li, Ye; Zhang, Chengmiao; Yin, Yin (Frontiers in Pharmacology, 2023)
Introduction: Immune checkpoint inhibitors (ICIs) exert antitumor responses in many types of cancer but may also induce serious or fatal toxicities that affect all organ systems, including the hematologic and lymphatic systems. However, the risk of hematologic and lymphatic system toxicities following different ICI treatments remains unknown. This study aimed to describe the hematologic and lymphatic system toxicities associated with different ICI regimens and the impact of combining ICIs with anti-vascular endothelial growth factor drugs using the US Food and Drug Administration Adverse Event Reporting System pharmacovigilance database. Methods: The reporting odds ratio (ROR) and information component (IC) indices were used to identify disproportionate reporting of ICI-associated hematologic and lymphatic adverse events (AEs). Results: We extracted 10,971 ICI-associated hematologic and lymphatic AEs from 35,417,155 reports. These AEs were more frequently reported in female patients (ROR: 1.04 95% confidence interval [CI]: 1.01–1.07) and younger patients (ROR: 1.05 95% CI: 1.01–1.09). The disseminated intravascular coagulation fatality rate (63.97%) was the highest among the reported preferred terms, despite its low incidence (3.32%). The time to onset of ICI-related hematologic and lymphatic AEs was relatively short, with 77.44% reported within 3 months. Disproportionate analysis showed that most ICIs were associated with significant overreporting of hematologic and lymphatic AEs (IC025: 0.34 and ROR025: 2.10). Hematologic and lymphatic system AEs were more frequently reported in patients treated with anti-programmed cell death protein 1/programmed cell death ligand 1 monotherapy than in those treated with anti-cytotoxic T-lymphocyte-associated protein 4 monotherapy (ROR: 1.54, 95% CI: 1.38–1.71), with atezolizumab showing the strongest signal (ROR025: 4.19, IC025: 1.00). In patients receiving combined treatment, ICIs plus bevacizumab exerted a higher disproportion signal than monotherapy (ROR: 161, 95% CI: 1.75–1.88). Discussion: The spectrum of hematologic and lymphatic AEs differed according to the ICI regimen. Early recognition and management of ICI-related hematologic and lymphatic AEs are vital in clinical practice.